Limitation of Doctor's Liability to Patients Based on the Value of Patient Safety - Leonardus Bayu Agung Prakoso; Slamet Suhartono (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to determine the comparison between students' mathematical critical thinking skills taught with macromedia flash interactive learning media compared to PowerPoint media. This type of research is an experimental research. This research was conducted at SD Negeri 101788 Marindal I. The population in this study was students of SD Negeri 101788 Marindal I. While the samples in this study were 27 students in class IV/a and 27 students in class IV/b. The data collection in this study used a mathematical critical thinking ability test. The research hypotheses were tested using independent sample t-test data analysis techniques. The results showed that: (1) There was a significant difference between students' mathematical critical thinking skills taught with interactive learning media macromedia flash compared to powerpoint media (Fcount = 4.005; sig. = 0.004); and (2) The average mathematical critical thinking ability of students who are taught with interactive learning media macromedia flash is higher than the powerpoint media with a Mean Difference value of 7.40. In other words, it can be said that there is a significant effect of the application of interactive learning media macromedia flash on students' mathematical critical thinking skills.